Defensive High‐Anxious Individuals Demonstrate Difference Responses to Pain Management to Those with Lower Levels of Defensiveness and Anxiety. Issue 2 (9th June 2017) - Franklin, Zoe C.; Fowler, Neil. E.
Abstract: Objectives: Few studies have considered the effect of Weinberger et al.'s personality types on the management of pain. The aims of this study were to (1) identify whether the relationships between pain intensity, cognitive factors, and disability at 3 and 6 months postbaseline differ as a result of personality type; and (2) identify whether personality type affects the likelihood of achieving a minimal clinically important change in pain intensity or disability at 3 and 6 months. Method: Patients completed a set of validated questionnaires assessing personality type, cognitive factors, pain intensity, and disability at 3 and 6 months postbaseline. Results: A greater proportion of defensive high‐anxious individuals reported improvement for both pain (3 months = 25%; 6 months = 38%) and disability (3 months = 35%; 6 months = 50%) and showed stronger links between improvements in pain and disability and baseline psychological factors than nonextreme individuals. Conclusions: The high proportion of defensive high‐anxious individuals highlights the need for psychologically based interventions to be delivered earlier in the care process. Stratifying the population, based on personality type, may allow for more targeted interventions, which could be more cost effective and reduce the number of patients remaining in the care system.